On the genus Urytalpa Edwards (Diptera: Keroplatidae) in the Nordic and Nearctic regions, with fixation of a new type species and a key to world males - Kjærandsen, Jostein; Martinsson, Svante; Hedmark, Kjell; Evenhuis, Neal L. (Zootaxa, 2009)
The five Nordic species of the genus Urytalpa Edwards (Diptera: Keroplatidae) are revised, of which one species, Urytalpa galdes Hedmark & Kjaerandsen, sp. n., is described as new to science based on males collected in northern Sweden. We find that the original type species assignment for Urytalpa (Platyura ochracea Meigen, 1818) is based on a misidentification, and in order to stabilize the nomenclature we therefore select a new type species, Urytalpa dorsalis (Staeger, 1840), sp. restit. A lectotype is designated for Orfelia ochracea (Meigen, 1818), comb. n. = Orfelia unicolor (Staeger, 1840), syn. n. The males of U. atriceps (Edwards, 1913), U. dorsalis, U. macrocera (Edwards, 1913) and U. trivittata (Lundström, 1914), and the females of U. dorsalis, U. macrocera and U. trivittata are described and illustrated based on Nordic material. As the first known Nearctic representative of Urytalpa, U. nigrita (Johannsen, 1910), comb. n., known from western USA (Washington) and Canada, is transferred from Pyrtaula to Urytalpa, illustrated and compared with the closely related U. rhapsodica Chandler, 1995 from central Europe. A key to all known males is provided. The generic limits of Urytalpa as presently understood are vague in relation to related genera and the genus is in need of a revision.